Pemberdayaan Kelompok melalui Konsep Silvofishery Penggemukan Kepiting di Dusun Tangkolak, Desa Sukakerta Karawang - Sam'un, Mohamad; Yusiana, Ekalia; Taryono, Taryono; Melani, Ana (Institut Pertanian Bogor, 2024)
The people of Tangkolak Sub-village have yet to manage the silvofishery concept in the mangrove forest area because knowledge and capital resources are limited. This service activity aims to provide knowledge and technology transfer, stimulants, and generate motivation and skills so that they can implement crab cultivation activities as an alternative business sector. Activities include delivering material offline, conducting question-and-answer discussions, and maintaining crabs. The target of the activity is the Joint Business Group (KUB) Kreasi Alam Bahari. The location of the activity is on the beach in East Tangkolak Hamlet, Sukakerta Village, Cilamaya Wetan District, Karawang Regency. This activity encourages mangrove forest conservation, provides technical material for cultivating crabs in mangrove forest areas, manages crab fattening farms, markets crabs through digital media, and implements crab cultivation practices in the Tangkolak mangrove forest area. Participants welcomed this activity because it met their expectations. As a result of the activities, training participants gained a better understanding of the benefits of a sustainable mangrove forest ecosystem, how to manage crab cultivation in mangrove areas, and experience carrying out crab cultivation procedures. The outcome is that local people can apply, become more experienced, and gain additional income from crab fattening.